PERBANDINGAN KUALITAS TELUR AYAM KAMPUNG YANG DISIMPAN PADA SUHU RUANG DAN SUHU LEMARI PENDINGIN DITINJAU DARI TINGGI KANTUNG HAWA, INDEKS KUNING TELUR, INDEKS ALBUMIN, HAUGH UNIT DAN TOTAL PLATE COUNT (TPC) - Juitaria Saly Inya Lupu; Diana A Wuri; Annytha I.R. Detha (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2016)
Local chicken egg is one of animal product coming from poultry livestock which practical to use. The local chicken egg can be influenced by temperature and keeping time. This research aims to know the comparison of local chicken egg quality which stored at room temperature and refrigerator temperature to air sac egg, yolk indeks, albumin indeks, Haugh Unit and TPC. There are 36 sample of local chicken eggs 0 day which stored at room temperature and refrigerator temperature with 6 keeping variation time ( day 10, 13, 16, 19, 22 and 25) and 3 time restating. The result of this research are show that the best keeping time of local chicken egg which stored at room temperature is under 10 day and under 13 day for refrigerator temperature. The result of measure air sac egg, yolkindeks, albumin indeks, Haugh Unit and TPC are showed that local chicken egg which stored at refrigerator temperature have bette quality then room temperature. The conclusion is, local chicken egg which stores at refrigerator temperature is saved to consume if the age of egg is under 10 days, even though the local chicken egg which stored at room temperature is saved to consume if the egg is under 13 day.